Conhecimentos tácito e técnico: implementações na função prática de artefatos de apoio à venda de trabalhadores informais em São Luís-MA - LIMA, André Luís de Oliveira (2022)
The changes in the Brazilian economy had a great impact on the unemployment rate, reflecting an increase in the number of unemployed across the country. At the same time, informality also grows, motivated by the need for self-support. From self-employment, manifestations of informality arise characterized by improvisations, "gambiarras" and constructions that help in the sale of workers who resort to the streets, as in the case of the street vendor. Therefore, this research seeks to understand the knowledge involved in artifacts produced by individuals who do not have technical knowledge in design and use these productions to assist in the sale of products and services, aiming to generate implementations that contribute to the improvement of artifacts, taking into account criteria of the ergonomics and product design that can optimize the user-product relationship. Among the authors who approach these manifestations, discussing the relationship between design and unconscious production, the term Popular Base Design (DBP) was used in the research, relating it to the practical function (of use) of the artifacts found. In this way, the methodological process involved mapping the occurrences of artifacts related to BPD in the city of São Luís-MA and their initial classification based on their type (fixed or mobile), classes of products and services and their use, together with applications of Product Design and Engineering techniques to analyze the artifacts found. Taking an existing product as a parameter, we sought to use the Reverse Design approach, originated from Reverse Engineering, adapted to the Design Science Research research method, which studies a context and, through a new artifact, proposes changes. As a result, there is a methodological proposal adapted to the context of the street vendor and implementations, through this, in 3 (three) groups of artifacts with greater occurrence in the central regions of São Luís-MA, considering the technical knowledge for and the conditions of work for these sellers.